β-actin and γ-actin are each dispensable for auditory hair cell development but required for Stereocilia maintenance. - Benjamin J Perrin; Kevin J Sonnemann; James M Ervasti (PLoS Genetics)
Hair cell stereocilia structure depends on actin filaments composed of cytoplasmic β-actin and γ-actin isoforms. Mutations in either gene can lead to progressive hearing loss in humans. Since β-actin and γ-actin isoforms are 99% identical at the protein level, it is unclear whether each isoform has distinct cellular roles. Here, we compared the functions of β-actin and γ-actin in stereocilia formation and maintenance by generating mice conditionally knocked out for Actb or Actg1 in hair cells. We found that, although cytoplasmic actin is necessary, neither β-actin nor γ-actin is required for normal stereocilia development or auditory function in young animals. However, aging mice with β-actin- or γ-actin-deficient hair cells develop different patterns of progressive hearing loss and distinct pathogenic changes in stereocilia morphology, despite colocalization of the actin isoforms. These results demonstrate overlapping developmental roles but unique post-developmental functions for β-actin and γ-actin in maintaining hair cell stereocilia.